Ecologia e biologia populacional dos ermitões (Decapoda, Anomura) do litoral norte de Santa Catarina - Stanski, Gilson [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The increase in the fishing fleet in southern Brazil has contributed to decrease in landings of profitable shrimps and bycatch species. The aim of this study is to investigate the biodiversity and spatial-temporal distribution of anomuran crustaceans captured as bycatch in the non-selective fishery of shrimps on the northern coast of Santa Catarina state, Brazil. In addition, we analyzed the influence of environmental factors on the abundance patterns of studied species. Monthly trawls were conducted in Babitonga Bay from July 2010 through June 2011, using a shrimp boat outfitted with double-rig nets, at depths from 5 to 17 m. Ecological indices (species richness, diversity, dominance and evenness) and redundancy analysis were assessed to analyze the hermit community and their relation with environmental factors. A total of 647 individuals were collected, represented by three families, six genera and seven species. Isocheles sawayai showed the highest abundance, flowed by Loxopagurus loxocheles. Both species demonstrated a positive correlation with temperature and phi (smaller sediment grain size). The highest richness and the evenness value were estimated at the depth 17 m. Otherwise, the five meters deep has the lowest evenness because the high dominance of I. sawayai, resulting in a lower estimated diversity. In a period with lower temperature and higher salinity as July were registered higher levels of diversity, probably because the lower dominance of tropical species (I. sawayai) and the occupation of species distributed in offshore regions (Petrochirus diogenes, Dardanus insignis, Pagurus exilis). Thus, the capture effort designated in the shrimp fishery carried an important diversity of anomuran crustaceans and others animal species, showing a danger to the marine trophic web

O aumento da frota de pesca no sul do Brasil tem contribuído para a redução dos desembarques de camarões rentáveis e das espécies que compõe a fauna acompanhante. O objetivo deste estudo foi investigar a biodiversidade e distribuição espaço-temporal de crustáceos Anomura, capturados como fauna acompanhante na pesca não seletiva de camarão no litoral norte do estado de Santa Catarina, Brasil. Além disso, analisou-se a influência de fatores ambientais sobre os padrões de abundância das espécies estudadas. Arrastos mensais foram realizadas na área adjacente à Baía da Babitonga de julho de 2010 até junho de 2011, utilizando um barco de camarão equipado com redes double-rig, em profundidades de 5 a 17 m. Índices ecológicos (riqueza de espécies, diversidade, dominância e equitabilidade) e a análise de redundância foram usados para analisar a comunidade de ermitões e sua relação com os fatores ambientais. Um total de 647 indivíduos foi coletado, representado por três famílias, seis gêneros e sete espécies. Isocheles sawayai apresentou a maior abundância, seguido por Loxopagurus loxocheles. Ambas as espécies tiveram uma correlação positiva com a temperatura e Phi (granulometria fina). A maior riqueza e os mais altos valores de equitabilidade foram encontrados na profundidade de 17 m. Por outro lado, a profundidade de cinco metros teve o menor valor de equitabilidade, devido à alta dominância de I. sawayai, ocasionando uma baixa diversidade local. No período de menor temperatura e maior salinidade (julho) foram registrados os mais altos índices de diversidade, influenciados pela baixa dominância de espécies tropicais (I. sawayai) e pela presença de espécies que vivem mais afastadas da costa (Petrochirus diogenes, Dardanus insignis, Pagurus exilis). Portanto, o esforço de captura direcionada à pesca camaroneira extraí no litoral sul do Brasil uma diversidade considerável...
Keywords: Decapode (Crustaceo); Camarão - Pesca; Biodiversidade marinha; Distribuição espacial da população; Habitat (Ecologia); Marine biodiversity